Vkorc1 variation in house mice during warfarin and difenacoum field trials. Issue 3 (23rd April 2012) - Endepols, Stefan; Klemann, Nicole; Song, Ying; Kohn, Michael H
Abstract BACKGROUND: Field studies guided by genetic monitoring of Vkorc1 need to be done to implicate mutations conclusively with rodent control problems due to the presence of animals resistant to anticoagulant rodenticides. Rodent control success in relation to Vkorc1 genotypes in house mice (Mus musculus domesticus) was studied on two farms (I and II) in Germany. Tests were carried out to determine whether certain resistance profiles and Vkorc1 genotypes displayed dynamics over the course of sequential treatments with warfarin and difenacoum that were consistent with single nucleotide polymorphisms (SNPs) in Vkorc1 as indicators of resistance. RESULTS: On farms I and II, respectively, three (A to C) and two (A and B) types of control problem with anticoagulants (i.e. proxies for resistance) were encountered in spatially segregated subunits: A = none; B = control problems with warfarin but not with difenacoum; C = control problems with both anticoagulants. Unexpectedly, resistance was encountered in a population where only Vkorc1 wild‐type mice were detected. In addition, the Arg58Gly Vkorc1 variant was found not to correlate with observed control failures. CONCLUSION: Control problems were encountered that cannot be explained by Vkorc1 coding or intronic SNPs, and therefore are likely due to non‐coding Vkorc1 SNPs or due to other genetic or non‐genetic factors. © 2012 Society of Chemical Industry